100 KW POWER WIND TURBINE DESIGN AND NUMERICAL SIMULATION AT AVERAGE WIND SPEED 7 M/SECOND - Firdaus, Muhammad
Based on data from EBTKE in 2018, Indonesia has a wind energy potential of 60.6 GW. This final project aims to determine the design of a 100 kW wind turbine blade with an average wind speed of 7 m/s, to obtain performance by numerical simulation, and to determine the Annual Energy Production (AEP) of a wind turbine with working conditions in Indonesia. In determining the rotor geometry of the wind turbine, the NACA and DU series airfoils are used in the blade design. Variation of the airfoil, chord length, and twist angle along the blades based on the 5 MW NREL wind turbine reference. The results of 3D blade design images and wind turbine performance simulations are obtained using QBlade software which consists of simulations of Rotor BEM, Turbine BEM, QFEM, and FAST. The blade geometry is obtained with the input parameters of the chord length, twist angle, type of airfoil used, and the position of the airfoil span along the blade. The simulation results are obtained with input parameters in the form of rotor rotational speed, wind speed, and type of power control. The AEP value is determined based on wind speed frequency data from windPROSPECTING and the wind turbine power curve against wind speed from the simulation results. The result of the BEM Rotor simulation is a graph of the power coefficient (Cp) against the tip speed ratio (?). Turbine BEM simulation results in the form of a graph of rotor power (P) against wind speed (V). The QLLT simulation results are in the form of images of vortex/wake flow, Cp values, and rotor power for speeds of 4 m/s, 7 m/s, 11 m/s, 15 m/s, and 20 m/s at a rotational speed of 28.086 rpm. The simulation results show that the shape of the vortex or wake is more regular when the tip speed ratio is lower or the wind speed is higher. Based on the QFEM simulation results for V = 20 m/s and 28.086 rpm, the maximum blade tension is 28.26 MPa. For the FAST simulation results, the graph of Cp and rotor power against time is obtained and the maximum Cp value is 0.4749 until 0.4761 with a tip speed ratio = 7.5. The AEP value is obtained from 1.27 GWh until 1.33 GWh for various types of simulation results.